An Envelope Detector Based on Memristive Systems - Vavra, J.; Biolek, D. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The Bipolar Memristive Systems with Threshold (BMST) are promising building blocks for analog signal processing. The present work describes their use in designing an envelope detector that can, in particular, be applied in automatic amplitude stabilizers or in the field of computing units, classifiers, as well as in a number of various types of lowvoltage and low-power nonlinear systems for signal processing. The operation of the proposed circuit has been verified via PSpice simulations.